High-Quality Outdoor Learning 2022
DOI: 10.1007/978-3-031-04108-2_13
|View full text |Cite
|
Sign up to set email alerts
|

Fostering 21st Century Skills Through Autonomy Supportive Science Education Outside the Classroom

Abstract: The development of 21st century skills in or rather through science teaching is on the agenda of many national and international school reforms aiming at creating so-called 21st century classrooms. In this context autonomous learning and practical relevance of science classes have been identified as important features, and education outside the classroom (EOtC) has been described as one way of providing such enriched classroom settings. We explore the relative importance of the four basic psychological needs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Jung, Zimmerman and Land [77] describe such an increased situational interest when the students are confronted with novel and surprising conditions, as well as with open and varied tasks that trigger their interest. The practical relevance of the learning content in EOtC can prepare the students for challenges in the "real world" [78]. This has also been found in a recent study by Skalstad and Munkebye [79] who showed that children's interest in natural science activities increases in outdoor environments.…”
Section: The Need For Autonomymentioning
confidence: 57%
“…Jung, Zimmerman and Land [77] describe such an increased situational interest when the students are confronted with novel and surprising conditions, as well as with open and varied tasks that trigger their interest. The practical relevance of the learning content in EOtC can prepare the students for challenges in the "real world" [78]. This has also been found in a recent study by Skalstad and Munkebye [79] who showed that children's interest in natural science activities increases in outdoor environments.…”
Section: The Need For Autonomymentioning
confidence: 57%